(untitled) (Indian Journal of Contemporary Dentistry, 2022)
Background: Over the last few years, Three-dimensional (3-D) printing, and prototyping has gained popularity within medical and dental profession and among patients alike. 3-D printing is an additive manufacturing technique in which objects are formed by deposition of material layer by layer. 3-D printers are machines that produce representations of objects either planned with a CAD program or scanned with a 3-D scanner. This article highlights the evolution, benefits and application of 3-D printers in pediatric dentistry.